PROPHYLACTIC ASPECT OF HOMOEOPATHY AN OVERVIEW FROM ANCIENT TO MODERN ERA - Das, *Biswo Ranjan; Narayana, Ala (International Journal of Ayurveda and Pharma Research, 2019)
The age old aphorism that “an ounce of prevention is worth a pound of cure” crystallizes the essence of concept of prevention of diseases. Prevention is the most effective way to reduce the disease burden in a community. Preservation of the health, promotion of health, prolongation of life and minimization of the sufferings can be achieved through prevention. From the very earliest period of the history of medicine until the most recent times, search for absolute preventives of diseases has always occupied a large share of attention of those who occupied themselves with medical art. In recent times attempts have been made-with more or less success - to discover prophylactics. One of the most noted and successful of these is the introduction of vaccination by Jenner, in 1798, as prophylactic of small pox which worked to and marvelous extent. In fact it has almost wiped out small pox from the face of the earth. Hygienic prophylactics have greatly helped to reduce the incidence of diseases. Rule that guides homoeopathic physicians to the selection of remedy should also lead him to the discovery of prophylactic. In this article, a thorough study from Hahnemanian period to modern period being made and some researches highlighted to justify Homeopathic Prophylaxis.